A STUDY OF THE INFLUENCE OF EXTRACELLULAR VESICLES ON THE MORPHOFUNCTIONAL STATE OF THE ENDOMETRIUM IN VITRO - Оксана Александровна Мелкозерова; Ирина Викторовна Крутинь; Александра Юрьевна Храмцова; Мария Валерьевна Улитко; Алсу Фармутовна Мустафина (Мать и дитя в Кузбассе)
Despite the long history of assisted reproductive technologies (ART), the effectiveness of in vitro fertilization (IVF) programs remains at the level of 30-40%. Of great importance in the implantation process is the receptivity of the endometrium, that is, its ability to ensure the necessary stages of implantation.